Enhancing the Seventh Grade Students' Listening Achievement through Total Physical Response (TPR) Method at SMP Nurul Islam Jember - Oktavia, Fiska Nurrahma; Setyono, Budi; Hastuti, Asih Santi (Jurnal Edukasi, 2016)
The aims of this research were to increase the students’ listening skill achievement by using TPR method and to know how TPR method could help the students understand the listening task. The research design used was Classroom Action Research (CAR) that was conducted in two cycles. The research subjects were the students of VIIC class which were chosen purposively based on the result of the listening pre-test. The data was collected from the students’ listening test and field notes. Then, the data of listening test was analyzed quantitatively using formula and the data of field notes were analyzed qualitatively in the form of description. The data result showed that TPR method could help the students improve their listening skill because of its three key features; imperative drills implementation, the use of real objects and demonstration, and increasing the students’ enthusiasm. Keywords : Listening, Teaching Method, TPR, Physical Response